Influence of cryogenic lubrication on the tribological properties of Ti6Al4V and Inconel 718 alloys under extreme contact conditions. (26th February 2014) - Courbon, C.; Pusavec, F.; Dumont, F.; Rech, J.; Kopac, J.; Almqvist, Andreas; Hardell, Jens; Prakash, Braham
ABSTRACT The proposed paper is focusing on the influence of cryogenic lubrication on friction within the context of machining TiAl6V4 and Inconel 718 alloys with carbide cutting tools. Several wear improvements have been reported in the literature when using liquid or gas nitrogen as cooling‐lubrication fluids compared with dry machining or to conventional emulsion lubrication. However, it is always questionable whether cryogenic lubrication is responsible for a decrease in the cutting temperature or for a decrease in the friction coefficient at the contact interfaces and whether liquid nitrogen lubrication is more effective than gas nitrogen lubrication. In order to simulate the tribological conditions corresponding to those occurring at these interfaces under dry and cryogenic conditions, a specially designed open tribometer has been used to characterise macroscopic friction coefficient, heat transfer and adhesion in the contact for a large range of sliding velocities. Friction, cryogenic, superalloys, heat transfer and adhesion Copyright © 2014 John Wiley & Sons, Ltd.